2006
DOI: 10.1103/physrevlett.97.116102
|View full text |Cite
|
Sign up to set email alerts
|

Trapping-Mediated Chemisorption of Ethylene onSi(001)c(4×2)

Abstract: Adsorption of ethylene molecules on Si(001)-c(4 x 2) was studied using scanning tunneling microscopy at low temperatures. Ethylene molecules trapped at the surface at 50 K were imaged only after decay to chemisorption, each bonding to a Si dimer. Atomic-scale observations of temperature-dependent kinetics show that the decay exhibited Arrhenius behavior with the reaction barrier of 128 meV in clear evidence of the trapping-mediated chemisorption, however, with an anomalously small preexponential factor of 300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 26 publications
5
37
2
Order By: Relevance
“…This is in distinct contrast to many other organic adsorbates on Si(0 0 1), like for example ethylene, which adsorbs via such a mobile precursor state and therefore shows a strong temperature dependence in its adsorption behavior [19,25,[33][34][35][36]. For instance, low temperature STM measurements of the adsorption of ethylene on Si(0 0 1) show a completely different adsorption behavior when compared to room temperature results [20,24,34,11]. Also for acetylene with its triple bond, adsorption proceeds via a precursor state with the respective dependence on surface temperature [37].…”
Section: Discussionmentioning
confidence: 85%
“…This is in distinct contrast to many other organic adsorbates on Si(0 0 1), like for example ethylene, which adsorbs via such a mobile precursor state and therefore shows a strong temperature dependence in its adsorption behavior [19,25,[33][34][35][36]. For instance, low temperature STM measurements of the adsorption of ethylene on Si(0 0 1) show a completely different adsorption behavior when compared to room temperature results [20,24,34,11]. Also for acetylene with its triple bond, adsorption proceeds via a precursor state with the respective dependence on surface temperature [37].…”
Section: Discussionmentioning
confidence: 85%
“…From low-temperature STM experiments, ε a = 0.13 eV was deduced for ethylene/Si(0 0 1) [9]; thus the binding energy of the -complex intermediate of ethylene on silicon is ε d = 0.33 eV. Experimental values for the binding energy of datively bonded systems on Si(0 0 1) are available for tertiary amines, e.g., 1.1 eV was reported in the case of trimethyl amine on Si(0 0 1) [30].…”
Section: Discussionmentioning
confidence: 99%
“…The main focus of the experimental investigations lay on the adsorption configurations and mechanisms; in most cases the reaction was found to proceed via a metastable precursor or intermediate state. Information on the underlying potential energy curve can be obtained from experiments on the adsorption dynamics, however, such experiments were reported only for the most prominent systems, e. g., ethylene or acetylene on Si(0 0 1) [8][9][10]. It was shown that the adsorption dynamics of these overall non-activated reactions are governed by the presence of the intermediate state ( Figure 1) which thus can be investigated in detail.…”
Section: Introductionmentioning
confidence: 96%
“…Based on the results of the DFT calculations a stable π-precursor was supposed to be formed due to the interaction between an unsaturated hydrocarbon molecule and a silicon atom (three-membered π-complex precursor) [13]. Later, these π-precursors were observed experimentally [14]. The available experimental data [9][10][11][12][15][16][17][18][19] are ambiguous and, therefore, most of the theoretical works are focused on the quantum-chemical calculations of binding energies for the different adsorption configurations [5,[19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 98%